COMPRESSIVE CAPACITY OF HELICAL PILE FOUNDATION ON PEAT WITH VARIATION OF HELICAL PLATE DIAMETER - Adi, Sapria; Fatnanta, Ferry; Satibi, Syawal (Universitas Ibn Khaldun Bogor, 2022)
The use of helical foundations to support structures on peat soil is still a new method. Research is needed to develop this foundation. There are 6 types of helical foundation tested on peat soil. To study the effect of helical plate diameter, plate diameters were varied with sizes 25 cm (M), 35 cm (L), and 45 cm (G). Plate positions (1, 2, 3 plates) are designed at 300 mm spacing. The axial compression bearing capacity test is carried out based on the constant rate of penetration procedure. At the beginning of loading, the load increases significantly. At a certain descent, the load begins to decrease slowly. The load-settlement curve shows that the larger the plate diameter, the greater the load it can withstand. The largest bearing capacity is produced by the GGG 30 foundation (3 plates dia.45 cm), which is 10.83 kN. LLL 30 helical foundation (3 plates dia.30 cm) provides a bearing capacity of 7.14 kN. These results clearly explain that the increase in plate diameter is directly proportional to the increase in the axial compression bearing capacity.